Enhancing Agronomic Traits of Food Crops with Biofilm Biofertilizers: Promoting Sustainable Farming in Indonesia - A Systematic Review - Elisabeth Mora; Tualar Simarmata; Rija Sudirja (CV. Rayyan Dwi Bharata, 2023)
Intensive use of inorganic fertilizers causes damage to soil ecosystem and environment. While, the utilization of biofertilizers holds significant potential in enhancing soil health and increasing crop yields as a viable solution for achieving more sustainable agricultural practices. This literature review explores biofilm biofertilizers (BBF) and plant growth promoting rhizobacteria (PGPR), examining their applications in improving soil-plant health, growth, and productivity. Employing Systematic Literature Review (SLR) methodologies, scientific literature from 2012 to 2022 was analyzed following PRISMA guidelines. Reputable journals indexed in Google Scholar and E-Journal Springer were selected, and relevant keywords were used to gather primary references. Results demonstrate that PGPR from various genera (Serratia sp., Bacillus sp., Pseudomonas sp., Streptomyces sp., and Cyanobacteria) produce growth promoters like indole-3-acetic acid (IAA), gibberellins, ethylene, and cytokinins. Combining BBF with chemical fertilizer can reduce chemical usage by up to 48%, reducing reliance on them. BBF containing PGPR exhibit potential to enhance agronomic of food crops traits and promote sustainable farming practices in Indonesia.Keywords: Systematic review, Biofilm, Biofilm Biofertilizer, Sustainable farming, Indonesia